2016
DOI: 10.1111/plb.12441
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and functional traits of culturable microbiome members, including cyanobacteria in the rice phyllosphere

Abstract: The diversity and abundance of culturable microbiome members of the rice phyllosphere was investigated using cv. Pusa Punjab Basmati 1509. Both diversity and species richness of bacteria were significantly higher in plants in pots in a semi-controlled environment than those in fields. Application of fertilisers reduced both diversity and species richness in field-grown plants under a conventional flooded system of rice intensification (SRI) and in dry-seeded rice (DSR) modes. Sequence analyses of 16S rDNA of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 74 publications
2
40
0
2
Order By: Relevance
“…Their population was much influenced by the cultivation methods particularly under the SRI method, and our earlier reports demonstrated their beneficial effects on soil and plant attributes . In another study, Venkatachalam et al observed that the diversity of cyanobacteria on the surface of rice leaves was modified by the fertilizer application and two different modes of experimentation (pot vs. field experiments). Bodenhausen et al observed that leaf and endophytic root compartments do not differ significantly in their diversity, richness, and evenness; however, the community composition is different.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Their population was much influenced by the cultivation methods particularly under the SRI method, and our earlier reports demonstrated their beneficial effects on soil and plant attributes . In another study, Venkatachalam et al observed that the diversity of cyanobacteria on the surface of rice leaves was modified by the fertilizer application and two different modes of experimentation (pot vs. field experiments). Bodenhausen et al observed that leaf and endophytic root compartments do not differ significantly in their diversity, richness, and evenness; however, the community composition is different.…”
Section: Discussionmentioning
confidence: 91%
“…This is supported by the insignificant differences observed in the nitrogen content of leaves across treatments. Our previous study illustrated the nitrogen-fixing potential of rice phyllosphere isolates, particularly among the cyanobacterial members, after their enrichment under aerobic and anaerobic conditions [5]. Knief et al [7] detected the presence of genes encoding dinitrogenase and dinitrogenase reductase in the phyllosphere and also reported the presence of nitrogen fixing bacteria in the rice phyllosphere, although they were fewer, as compared to the rhizosphere.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The definition of large scale, in fact, has changed rapidly from hundreds [16] to tens of thousands [20] of strains. Recent plant-associated bacterial and fungal isolate collections (summarized in Table 1) are derived from sugarcane [20]; grapevine [2123]; potato [24]; tomato [25]; eucalyptus [25]; rice [26,27]; ancient wheat ancestors [19]; lettuce [28]; Arabidopsis [16, 29]; poplar [29]; and from plants growing in an arsenic-contaminated soils [30]. The increasing volume of isolate collections will tax existing repositories; yet the genomic diversity contained in the bacterial isolates that are being obtained is not nearing saturation [16].…”
Section: Screening Of Large Isolate Collectionsmentioning
confidence: 99%
“…Even though several studies have characterized the bacterial community in phyllosphere of plants of tropical forests, reports on cyanobacteria community composition in the phyllosphere are scarce (Fürnkranz et al 2008, Rigonato et al 2012, Alvarenga et al, 2016, Venkatachalam et al, 2016. Herein, the community structure of cyanobacteria inhabiting phyllosphere of four plant species from the Brazilian Atlantic Forest biome was accessed using cultivationindependent molecular approaches.…”
Section: Introductionmentioning
confidence: 97%